Surprising Conformers of the Biologically Important A·T DNA Base Pairs: QM/QTAIM Proofs - Brovarets', Ol'ha O.; Tsiupa, Kostiantyn S.; Hovorun, Dmytro M. (Frontiers in Chemistry, 2018)
For the first time novel high-energy conformers–A·T(wWC) (5.36), A·T(wrWC) (5.97), A·T(wH) (5.78), and A·T(wrH) (ΔG = 5.82 kcal·mol−1) (See Graphical Abstract) were revealed for each of the four biologically important A·T DNA base pairs – Watson-Crick A·T(WC), reverse Watson-Crick A·T(rWC), Hoogsteen A·T(H) and reverse Hoogsteen A·T(rH) at the MP2/aug-cc-pVDZ//B3LYP/6-311++G(d,p) level of quantum-mechanical theory in the continuum with ε = 4 under normal conditions. Each of these conformers possesses substantially non-planar wobble (w) structure and is stabilized by the participation of the two anti-parallel N6H/N6H′…O4/O2 and N3H…N6 H-bonds, involving the pyramidalized amino group of the A DNA base as an acceptor and a donor of the H-bonding. The transition states – TSA·T(WC)↔A·T(wWC), TSA·T(rWC)↔A·T(wrWC), TSA·T(H)↔A·T(wH), and TSA·T(rH)↔A·T(wrH), controlling the dipole-active transformations of the conformers from the main plane-symmetric state into the high-energy, significantly non-planar state and vice versa, were localized. They also possess wobble structures similarly to the high-energy conformers and are stabilized by the participation of the N6H/N6H′…O4/O2 and N3H…N6 H-bonds. Discovered conformers of the A·T DNA base pairs are dynamically stable short-lived structures [lifetime τ = (1.4–3.9) ps]. Their possible biological significance and future perspectives have been briefly discussed.